Rapid Onset of Cutaneous Adverse Drug Reaction to 2HPMZ/2HPM: A Case Report - Widiarto, Pandu; Azzumar, Farchan; Putriana, Khansa; Burhan, Erlina (Jurnal Respirologi Indonesia, 2026)
Background: The World Health Organization (WHO) has endorsed the 4-month tuberculosis (TB) regimen, 2HPMZ/2HPM (Isoniazid, Rifapentine, Moxifloxacin, Pyrazinamide), as a non-inferior alternative to the standard six-month course, representing a major advancement in global TB control. While large clinical trials established its general safety, real-world data and management on its adverse drug reaction (ADR), particularly cutaneous adverse drug reactions (CADRs), remains limited.  Case Presentation: We present a case of a 19-year-old male initiated on the 2HPMZ/2HPM regimen for pulmonary TB. Within 30 minutes of treatment initiation, the patient developed a maculopapular erythematous rash on both arms and legs. Given the mild degree, the treatment is continued along with Cetirizine and Prednisone administration.  Discussion: CADR is the most common and visible ADR of Anti Tuberculosis Drugs. The clinical severity of ADR extends from mild, severe, to life-threatening, however, most of the CADRs are mild. Grading the CADR is very important to determine proper management. In this case, continuing treatment after mild CADR is demonstrated to be safe and sufficient. Conclusion: Our experience demonstrates the safety and feasibility of maintaining the full 2HPMZ/2HPM regimen despite mild cutaneous manifestations, thus avoiding treatment interruption, the need for complex re-challenge protocols, and potential treatment failure.